2003
DOI: 10.1021/ja0353762
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Iridium-Catalyzed Hydrogenation of Heteroaromatic Compounds, Quinolines

Abstract: Catalytic asymmetric hydrogenations of prochiral unsaturated compounds, such as olefin, ketone, and imine, have been intensively studied and are considered as a versatile method of creating a chiral carbon center. 1 However, asymmetric hydrogenation of heteroaromatic compounds is less explored, resonance stability of heteroaromatic compounds might impede the enantioselective hydrogenation. 2 To date, only a few papers on homogeneous asymmetric hydrogenation of heteroaromatic compounds have been reported. Kuwan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
186
1
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 539 publications
(198 citation statements)
references
References 19 publications
1
186
1
10
Order By: Relevance
“…Using 2-methylquinoline as a model substrate, the reaction proceeded smoothly, affording 2-methyl-1,2,3,4-tetrahydroquinoline with 94% ee (Scheme 4). 11 After screening several other additives, we concluded that only iodine and halogen analogues give excellent conversions and enantioselectivity.…”
Section: Asymmetric Hydrogenation Of Quinoline and Isoquinoline Derivmentioning
confidence: 95%
See 1 more Smart Citation
“…Using 2-methylquinoline as a model substrate, the reaction proceeded smoothly, affording 2-methyl-1,2,3,4-tetrahydroquinoline with 94% ee (Scheme 4). 11 After screening several other additives, we concluded that only iodine and halogen analogues give excellent conversions and enantioselectivity.…”
Section: Asymmetric Hydrogenation Of Quinoline and Isoquinoline Derivmentioning
confidence: 95%
“…This methodology can be successfully applied to the asymmetric synthesis of tetrahydroquinoline alkaloids and chiral drugs (Scheme 6). 11,13 For example, the hydrogenation product of 6-fluoro-2-methylquinoline is the key intermediate of the antibacterial agent of Flumequine. N-Methylation of hydrogenation products completed the synthesis of angustrureine, galipinine, and cuspareine in high total yields.…”
Section: Asymmetric Hydrogenation Of Quinoline and Isoquinoline Derivmentioning
confidence: 99%
“…Zhou and co-workers reported the first highly enantioselective iridium-catalyzed hydrogenation of quinolines 10 (Scheme 14). [42] The optimal reaction conditions found were [IrClA C H T U N G T R E N N U N G (cod)] 2 together with a ligand possessing axial chirality, (R)-MeO-BiPhep (39), and iodine as the additive. A number of tetrahydroquinolines were prepared with excellent ee values (up to 96 %).…”
mentioning
confidence: 99%
“…A number of tetrahydroquinolines were prepared with excellent ee values (up to 96 %). Four products were further transformed into natural alkaloids: galipinine (40), angustureine (41), cuspareine (42), and the antibacterial agent flumequine (43). The catalyst was successfully immobilized on a soluble PEG polymer support by replacing one of the OMe groups by MeO-PEG-(1600).…”
mentioning
confidence: 99%
See 1 more Smart Citation